Species Delimitation in the Genus Lepisorus (Polypodiaceae): Implications for Adaptation, Ecology, and Distribution on Evolutionary Diversification - Violanda Aldila Rahayu; Mildawati Mildawati (Jurnal Biologi Tropis, 2026)
The genus Lepisorus (Polypodiaceae) exhibits high morphological, ecological, and genetic diversity, often complicating species delimitation based on single lines of evidence. This study synthesized evidence on ecological adaptation, distribution patterns, and the genetic mechanisms underlying diversification in Lepisorus through a systematic review of primary articles published between 2015 and 2025, retrieved from major international databases. The results indicate close evolutionary relationships between Lepisorus waltonii and L. clathratus based on chloroplast genome data, while L. scolopendrium and L. bicolor exhibit pronounced ecological plasticity associated with habitat disturbance. Cytological variation, including diploid and tetraploid cytotypes within the L. clathratus complex, correlates with elevational distribution and environmental tolerance. Additionally, polyploidy and hybridization in L. nigripes and L. yamaokae contribute to the diversification of their lineages. These findings underscore the need for an integrative taxonomic approach that combines morphological, molecular, cytological, and ecological data to accurately delimit species in Lepisorus.